Molecular analysis of a fungal disease in the habitat‐forming brown macroalga Phyllospora comosa (Fucales) along a latitudinal gradient. Issue 5 (26th May 2021) - Ferrari, Juliana; Goncalves, Priscila; Campbell, Alexandra Helene; Sudatti, Daniela Bueno; Wood, Georgina Valentine; Thomas, Torsten; Pereira, Renato Crespo; Steinberg, Peter David; Marzinelli, Ezequiel Miguel
Abstract : Infectious diseases affecting habitat‐forming species can have significant impacts on population dynamics and alter the structure and functioning of marine ecosystems. Recently, a fungal infection was described as the causative agent of necrotic lesions on the stipe of the forest‐forming macroalga Phyllospora comosa, a disease named "stipe rot" (SR). Here, we developed a quantitative PCR (qPCR) method for rapid detection and quantification of this pathogen, which was applied to evaluate the level of SR infection in eight P . comosa populations spanning the entire latitudinal distribution of this species along southeastern Australia. We also investigated the relationship between the abundance and prevalence of Stipe Rot Fungus (SRF) and potential host chemical defenses as well as its relationship with morphological and ecophysiological traits of P . comosa . qPCR estimates of SRF abundance reflected the levels of infection estimated by visual assessment, with higher numbers of SRF copies being observed in individuals showing high or intermediate levels of visual symptoms of SR. Concordance of conventional PCR and visual assessments was 92 and 94%, respectively, compared to qPCR detection. SRF prevalence was positively related to fucoxanthin content and herbivory, but not significant related to other traits measured (phlorotannin content, total length, thallus diameter, stipe width, number of branches, frond width, fouling, bleaching, gender, and photosynthetic efficiency). These results provide confidence for previous reports of this disease based upon visual assessments only, contribute to the development of monitoring and conservation strategies for safeguarding P . comosa forests, and generate insights into potential factors influencing host–pathogen interactions in this system.